Factores asociados a la desnutrición en niños atendidos en un hospital pediátrico de Angola: Factors associated with malnutrition in children treated at a pediatric hospital in Angola - Ruiz-Piedra, Alina Maria (2024)
Malnutrition has serious consequences for children by affecting their growth and development. Objective: To identify the factors associated with malnutrition in children under five years of age. Materials and methods: observational, analytical, cross-sectional and retrospective study. Theoretical, empirical and mathematical statistical methods were applied. Study population: children under 5 years of age treated at the pediatric hospital in Menongue, Angola, between January and March 2023 (n=211). Exclusion criteria: terminally ill children, incomplete medical records, and responsible persons who did not agree to participate in the study. Statistical treatment: the group composition variable was the child's weight, with two categories: malnourished (N=138) and normal weight (N=73). Chi-square, Mann-Whitney U and Odd Ratio (OR) tests were applied with 95% significance. Results: The largest number of children attended was in the age group of 1 – 2 years (140 children), 64.5% malnourished and 75.3% normal weight. Statistically significant differences between the two groups were observed in single marital status (p=0.000), primary school level (p=0.007), father's presence and education (p=0.012), house with untreated water (p=0.007), age (p=0.000), weight (p=0000) and Body Mass Index (BMI) (p=0.000). The risk factors identified were having untreated water at home (OR=1.3) and the presence of the father (OR=0.77), being a married mother (OR=0.75) as protectors. Conclusions: There are social and economic factors associated with malnutrition in children under five years of age.